Comparison of Two Different Cut-Off Values of Scoring System for Diagnosis of Hirschsprung-Associated Enterocolitis After Transanal Endorectal Pull-Through - Gunadi,; Luzman, Raedi Ardlo; Kencana, Sagita Mega Sekar; Arthana, Bhagas Dwi; Ahmad, Fauzan; Sulaksmono, Ganjar; Rastaputra, Agitha Swandaru; Arini, Golda Puspa; Pitaka, Ririd Tri; Dwihantoro, Andi; Makhmudi, Akhmad (Frontiers in Pediatrics, 2021)
Background: Hirschsprung-associated enterocolitis (HAEC) is a major contributor in the mortality of Hirschsprung disease (HSCR) patients that can occur both preoperatively and postoperatively. Several cut-off values of HAEC score have been used, i.e. ≥10 and ≥4. Here, we compared the HAEC frequency after transanal endorectal pull-through (TEPT) using two cut-offs of scoring system and associated them with the risk factors. Methods: Cross-sectional analysis was conducted using medical records of HSCR patients who were aged ≤ 18 years old and underwent TEPT at our institution, Indonesia between 2009 and 2016. HAEC was determined using the scoring system with cut-off values of ≥10 and ≥4. Results: Seventy subjects were used in the final analysis, consisting of 44 males and 26 females. There was a significant difference in one HAEC finding between the ≥10 and ≥4 cut-off groups; diarrhea with explosive stools (p=0.002). The HAEC frequency was 5/70 (7.1%) and 49/70 (70%) patients using cut-off values of ≥10 and ≥4 (p<0.0001), respectively. We found that patients with anemia (i.e. iron deficiency anemia) had a higher risk of HAEC after TEPT than patients with normal hemoglobin level with OR of 3.77 (95% CI=1.28 – 11.1; p=0.027), while no associations were found between other variables, including sex, age at diagnosis, age at definitive therapy, albumin level, and nutritional status and HAEC following TEPT (p=0.87, 0.15, 0.33, 0.26, and 0.60, respectively). Also, no associations were observed between maternal education level, mother’s age at pregnancy and gestational age and HAEC after definitive surgery (p=0.10, 0.46, and 0.86, respectively). Conclusions: This report is the first study comparing two different cut-off values of scoring system to evaluate the HAEC frequency after TEPT and results suggest further using cut-off of ≥4 to expand the diagnosis of HAEC. Moreover, we also show for the first time that hemoglobin level is a strong risk factor for the HAEC development after TEPT